Cloning, purification, crystallization and preliminary crystallographic analysis of the human histone deacetylase sirtuin 1 - Holbourn, Kenneth P. (International Union of Crystallography, 2011)
Human sirtuin 1 is a member of the histone deacetylase family and is involved in cellular aging, tumourigenesis and cellular metabolism. Recombinant sirtuin 1 comprising residues 140–747 was crystallized using the hanging-drop vapour-diffusion method. The crystal diffracted to 3.4 Å resolution and belonged to space group P622, with unit-cell parameters a = b = 203.1, c = 625.3 Å, and is estimated to contain between six and 12 molecules per asymmetric unit.